2019
DOI: 10.1073/pnas.1907042116
|View full text |Cite
|
Sign up to set email alerts
|

A small number of cholinergic neurons mediate hyperaggression in female Drosophila

Abstract: In the Drosophila model of aggression, males and females fight in same-sex pairings, but a wide disparity exists in the levels of aggression displayed by the 2 sexes. A screen of Drosophila Flylight Gal4 lines by driving expression of the gene coding for the temperature sensitive dTRPA1 channel, yielded a single line (GMR26E01-Gal4) displaying greatly enhanced aggression when thermoactivated. Targeted neurons were widely distributed throughout male and female nervous systems, but the enhanced aggression was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 42 publications
1
46
2
Order By: Relevance
“…No expression was observed in males in the majority of the lines used ( Figure 4 The cells labeled in males in two of the lines were not morphologically similar to pC1d or pC1e and these lines were not used for behavioral analysis in males. RNAseq analysis of pC1d and pC1e neurons confirmed that the cells expressed dsx and a gene associated with use of acetylcholine (ChAT) ( Figure 1-figure supplement 5), as previously described (Palavicino-Maggio et al, 2019;Rezával et al, 2016;Rideout et al, 2010;Zhou et al, 2014). Our data suggest that these cells might also express fru (Figure 1-figure supplement 5).…”
Section: Activation Of Pc1d Alone But Not Pc1e or Pc1a -C Promotes supporting
confidence: 84%
See 1 more Smart Citation
“…No expression was observed in males in the majority of the lines used ( Figure 4 The cells labeled in males in two of the lines were not morphologically similar to pC1d or pC1e and these lines were not used for behavioral analysis in males. RNAseq analysis of pC1d and pC1e neurons confirmed that the cells expressed dsx and a gene associated with use of acetylcholine (ChAT) ( Figure 1-figure supplement 5), as previously described (Palavicino-Maggio et al, 2019;Rezával et al, 2016;Rideout et al, 2010;Zhou et al, 2014). Our data suggest that these cells might also express fru (Figure 1-figure supplement 5).…”
Section: Activation Of Pc1d Alone But Not Pc1e or Pc1a -C Promotes supporting
confidence: 84%
“…Optogenetic activation dramatically increased aggression in lines labelling aIPg neurons, while inactivation diminished these actions. Analysis using EM-level connectomics revealed strong connectivity between these aIPg neurons and two members of the pC1 cluster, a group of related cell types previously linked to social behaviors (Hoopfer et al, 2015;Palavicino-Maggio et al, 2019;Wang et al, 2020;Zhou et al, 2014). In particular, pC1d is the top pre-synaptic input to aIPg neurons, devoting ~13% of its output synapses to them.…”
Section: Discussionmentioning
confidence: 99%
“…Thermogenetic activation of pC1 neurons in females drives chasing (Rezával et al, 2016;Wu et al, 2019), a male-specific behavior, and also aggressive behaviors toward females (Palavicino-Maggio et al, 2019). Taken together these data suggest that female pC1 neurons can drive multiple distinct behaviors, similar to male P1 neurons, but whether female pC1 neurons can drive persistent changes in behavior and persistent neural activity, has not yet been investigated.…”
Section: Introductionmentioning
confidence: 94%
“…In sum, we found that for minutes following pC1-Int activation, females produced a variety of behaviors directed at the male. Some of these appear aggressive, such as shoving and headbutting (Nilsen et al, 2004;Palavicino-Maggio et al, 2019), while others resemble male courtship behaviors, such as chasing and unilateral wing extension. These behaviors typically peaked in the d3 condition, where they remained high 30 minutes after male introduction.…”
Section: Female Pc1 Activation Drives Persistent Female Shoving and Cmentioning
confidence: 99%
See 1 more Smart Citation